Pengembangan Game Edukasi Gerabah-Rush sebagai Game Unggulan Industri Gerabah Pagelaran - Iriaji; Ike Ratnawati; Abdul Rahman Prasetyo; Alby Aruna; Eka Putri Surya; Adinda Marcelliantika; Ginanjar Atma Wijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This community service program aims to develop the educational game